Endangered Mexico an environment on the edge - Simon, Joel (Sierra Club Books, 1997)
Mexico City's air, the world's worst, is one of the most notorious urban environmental problems of our time. Yet such severe air pollution is merely one of a number of serious environmental threats - including chronic water shortages, eroding farmland, and a massive depletion of natural resources - which have turned Mexico into an international political and economic crisis waiting to happen. Combining historical research with extensive personal interviews, Joel Simon uncovers the connection between Mexico's environment and its present social and political instability. Interviews with businesspeople, bureaucrats, environmentalists, and citizens reinforce historical data which suggests that if Mexican society continues on its present course of economic development, it cannot avoid political catastrophe. Endangered Mexico offers revealing insights into Mexico's history, its ambitions, and its complex relationship with the United States.